THE ROLE OF UNDIFFERENTIATED CONNECTIVE TISSUE DYSPLASIA IN THE DEVELOPMENT OF GENITAL PROLAPSE IN WOMEN OF REPRODUCTIVE AGE - Urinova R.Sh.; Saidjalilova D.D.; Ayupova D.A.; Khodjaeva D.N. (Scholar Express Journals, 2023)
The article studies and evaluates the level of hydroxyproline in the daily urine of women with genital prolapse against the background of undifferentiated connective tissue dysplasia, which makes it possible to judge the state of collagen metabolism in diseases accompanied by destructive processes in the connective tissue. In women with genital prolapse, 57.1% had undifferentiated connective tissue dysplasia
Keywords: study; uCTD; prolapse; collagen